2014
DOI: 10.1007/s00604-014-1334-2
|View full text |Cite
|
Sign up to set email alerts
|

Two-layer reflectometric interference spectroscopy-based immunosensing for C-reactive protein

Abstract: We report on dual interference layers for use in reflectometric interference spectroscopy (RIfS)-based immunosensing. The layers consist of (a) an antibodyembedded organic/inorganic hybrid titanium dioxide (TiO 2 ) layer (~60 nm thick) as a sensitive layer, and (b) a TiO 2 layer (~110 nm thick) as an interference base layer placed on a silicone substrate by liquid phase deposition. A monoclonal antibody against C-reactive protein (anti-CRP) was coembedded with poly(L-lysine) as an organic binder during deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…The sensitivity of this system is therefore ten times larger than our previous report of 50 ng mL À1 . [14][15][16] These results suggested that the thickness difference affected the CRP binding behavior via SPR measurement, and in this study, PMPC layer with 4.6 nm of thickness showed the sensitive and accurate detection for CRP.…”
Section: -3 Comparison Of Crp Binding Behavior In Two Different Pmpc ...supporting
confidence: 53%
See 2 more Smart Citations
“…The sensitivity of this system is therefore ten times larger than our previous report of 50 ng mL À1 . [14][15][16] These results suggested that the thickness difference affected the CRP binding behavior via SPR measurement, and in this study, PMPC layer with 4.6 nm of thickness showed the sensitive and accurate detection for CRP.…”
Section: -3 Comparison Of Crp Binding Behavior In Two Different Pmpc ...supporting
confidence: 53%
“…8,9 However, these methods are limited to a threshold of 0.3 mg mL À1 . [14][15][16] Although using antibody recognition elements enables highly sensitive and selective detection of target proteins, the production and purification of the antibodies are complex and expensive. [10][11][12][13] In addition, we have reported highly sensitive CRP detection with an anti-CRP immobilized substrate utilizing surface plasmon resonance (SPR) and reflectometric interference spectroscopy, with a limit of detection (LOD) of 50 ng mL À1 having been achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further applications are the quantification of sarcosine [360], the determination of myoglobin at 0.1 mg L-1 by immobilizing the antibody via histidine-tagged recombinant protein A [361], or the analysis of biological toxins and E. coli ( [362]. By optimizing the layer system C-reactive protein was measured [363].…”
Section: Reflectometric Interference Spectroscopymentioning
confidence: 99%
“…560 pM, respectively. 15,16 We recently demonstrated the highly sensitive detection of CRP based on non-immunological interactions. 17,18 The phosphorylcholine group is a specific ligand for CRP in the presence of Ca 2+ ions [19][20][21] and thus our methodology utilizes protein-ligand interactions between a polymeric ligand, poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC), and CRP.…”
mentioning
confidence: 99%